Human resource management strategy in facing organizational change in pelambik village - Wulandari, Yayang Erry (Law and Economics, 2025)
This study aims to analyze the strategy of Human Resource Management (HRM) in dealing with organizational changes in Pelambik Village. The changes that occurred include restructuring village apparatus, digitizing administration, strengthening work culture, and community involvement in program planning and evaluation. The study used a descriptive qualitative approach with purposive sampling techniques to select informants including village officials, administrative staff, community leaders, and residents affected by the change. Data was collected through in-depth interviews, observations, and documentation, then analyzed in a thematic descriptive manner. The results of the study show that the HRM strategy which includes competency development, effective internal communication, motivation and rewards, mentoring, teamwork, and continuous evaluation has succeeded in supporting the adaptation of village apparatus to organizational changes. The successful implementation of the HRM strategy is influenced by visionary leadership, budget support, adequate technological infrastructure, adaptive organizational culture, human resource competence and motivation, and active community participation. This research emphasizes that a comprehensive HRM strategy is able to ensure that organizational transformation runs harmoniously, adaptively, and sustainably, as well as being an example of effective HRM practices at the village level. These findings make an academic and practical contribution to the development of HRM strategies in local government settings.